Analysis Of Cpu And Memory Usage In Monitoring-Based Operating Systems Using Python - Alviyyah Julianti; Teti Desyani; Tasya Putri Aini; Irvan Maulana; Didin Nugraha; Rayhan Frenalzy (International Journal of Health Engineering and Technology, 2026)
Monitoring computer resource usage, particularly the central processing unit (CPU) and memory, is a crucial aspect in maintaining the performance and stability of an operating system. This study aims to analyze CPU and memory usage in real-time using the Python programming language as the primary tool. The method used involves collecting system resource usage data through Python libraries, such as psutil, followed by data processing and visualization to obtain an overview of usage patterns. The results show that Python is capable of providing accurate and efficient information regarding CPU and memory usage conditions, thus providing a basis for decision-making to optimize system performance. Furthermore, the developed monitoring system is flexible, easy to use, and can be implemented on various operating system platforms. Therefore, this study is expected to contribute to the development of a simple yet effective resource monitoring system. (Monitoring computer resource usage, particularly the central processing unit (CPU) and memory, is a crucial aspect in maintaining the performance and stability of an operating system. This study aims to analyze CPU, and memory usage in real time using the Python programming language as the primary tool. The method used involves collecting system resource usage data through Python libraries, such as psutil, followed by data processing and visualization to obtain an overview of usage patterns. The results show that Python is capable of providing accurate and efficient information regarding CPU and memory usage conditions, thus providing a basis for decision-making to optimize system performance. Furthermore, the developed monitoring system is flexible, easy to use, and can be implemented on various operating system platforms. Thus, this research is expected to contribute to the development of a simple yet effective resource monitoring system.